2006
DOI: 10.1007/s00787-006-0508-9
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and language impairment

Abstract: The parental questionnaire FTF (Five to Fifteen) was given to parents of 76 children (mean age 11 years) diagnosed with ADHD. About half of the children had at least once been referred to a speech- and language pathologist. Most of them had not received any intervention or follow-up. A factor analysis identified six problem areas, which explain close to 75% of the total variation: Cognitive Skills, Motor/Perception, Emotion/Socialisation/Behaviour, Attention, Literacy Skills and Activity Control. The majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(63 citation statements)
references
References 18 publications
4
56
1
2
Order By: Relevance
“…Especially the amount of impulsivity characteristics affects the language abilities, including language form and pragmatics. It was already known that children with ADHD often encounter all types of language deficiencies (Study 1, Baird et al 2000;Bruce et al 2006;Oram et al 1999;Tannock and Schachar 1996) and that children with language disorders at early age are at risk of developing ASD or ADHD like behavior; some do even receive a psychiatric diagnosis at older age (Miniscalco et al 2006;Snowling et al 2006). However, it might be that both impulsivity and the language disorder(s) are already present in early development and that the combination and/or corroboration of these two leads to the emergence of a full blown developmental disorder later in life.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Especially the amount of impulsivity characteristics affects the language abilities, including language form and pragmatics. It was already known that children with ADHD often encounter all types of language deficiencies (Study 1, Baird et al 2000;Bruce et al 2006;Oram et al 1999;Tannock and Schachar 1996) and that children with language disorders at early age are at risk of developing ASD or ADHD like behavior; some do even receive a psychiatric diagnosis at older age (Miniscalco et al 2006;Snowling et al 2006). However, it might be that both impulsivity and the language disorder(s) are already present in early development and that the combination and/or corroboration of these two leads to the emergence of a full blown developmental disorder later in life.…”
Section: Discussionmentioning
confidence: 97%
“…Language disorders are often present in children with attention deficit hyperactivity disorder (ADHD; e.g., Baird et al 2000;Bruce et al 2006;Oram et al 1999;Tannock and Schachar 1996). However, the cardinal features of ADHD are inattentiveness, hyperactivity, and impulsivity (APA 2000) and language related impairments are not required to fulfill criteria of ADHD.…”
Section: Communication Difficulties In Adhdmentioning
confidence: 99%
“…In contrast, the potential influence of verbal/nonverbal limitations on victimization status in children with ADHD is unknown because investigations have not included developmental assessments in these areas. This gap is unfortunate in light of reports suggesting that LI and attention deficits frequently co-occur, and that a significant portion of children with ADHD have undiagnosed LI contributing to their social and academic difficulties (Bruce, Thernlund, & Nettelbladt, 2006; Cohen, Davine, Horodezky, Lipsett, & Isaacson, 1993; Love & Thompson, 1988; Tirosh & Cohen, 1998; for confuting evidence, see Cardy, Tannock, Johnson, & Johnson, 2010; Luo & Timler, 2008; Redmond, 2004). …”
mentioning
confidence: 99%
“…A study by Estrem (2005) confirmed connection between problem behavior and language development, documenting that observed aggression increased as expressive and receptive language scores decreased in 100 preschoolers. Other studies (Bruce, 2006;Beitchman et al, 2001;Cohen et al, 2000) have also revealed a significant interrelationship between language disorders, attention deficit disorders and autism spectrum disorders.…”
Section: International Journal Of Educationmentioning
confidence: 96%